The moderating effect of self-efficacy on the relationship between social capital and social well-being among youth - Ahmad Iqbal, Mian Muhammad (2022)
The purpose of this study is to examine the moderating effect of self-efficacy on the relationship between social capital and social well-being. In particular, this research aims to examine the demographic characteristics of the Pakistani youth in Punjab and the moderating effect of self-efficacy, on the relationship between various types of social capital (bonding, bridging and linking) and social well-being. The disparities in respondents' social well-being based on their demographic profile will also be investigated. This study adopted the quantitative research design. Using a multistage sampling strategy, data from 852 students enrolled in selected public universities in Punjab, Pakistan, were obtained for this study. The findings reveal that bonding, bridging, and linking types of social capital are positively associated with social well-being. In terms of the moderating hypothesis, self-efficacy moderates the relationship between bonding and bridging social capital and social well-being. Likewise, self-efficacy does not simplify the relationship between social capital and social well-being. Additionally, comparative analysis revealed that the respondents’ social well-being differs according to their gender, marital status, type of family, age, study program, and monthly household income. The number of family members, friends in the community, friends on social media, and average time spent on social media are other factors that contribute to this disparity. This study concludes that the Pakistani government should invest in the youth’s social capital, self-efficacy, and social well-being, which are essential for the country's development and the elimination of socioeconomic inequalities.